Phase-locked loop based synchronization schemes for three-phase unbalanced and distorted grid: a review - Tripathy, Poonam; Misra, Banishree; Nayak, Byamakesh (International Journal of Applied Power Engineering (IJAPE), 2024)
The rapidly growing dispersion of distributed generation systems into the utility grid needs appropriate control techniques to stay interconnected even under abnormal and distorted grid conditions to ensure the overall grid stability. To avoid the loss of renewable energy sources (RES) based power generation, the disintegration of RES with respect to synchronization issues must be prohibited for efficient operation. RES control highly relies on the synchronization technique as it is faster and accurate enough to detect the utility grid variables in terms of amplitude, phase, and frequency. Mostly, the phase-locked loop (PLL) synchronization schemes are utilized for control of RES and monitoring of grid voltage. The dynamics of the grid side converter (GSC) is directly influenced by the performance and design criteria of the PLLs. This paper proposes an overall review of the performances of three phase PLL based grid synchronization methods under diverse weak grid conditions.